Eskatologi Islam: Doktrin Surga dan Neraka Dalam Kitab Daqāiq al-Akhbār Fī Dzikri al-Jannat wa an-Nār - Muhammad Ihza Fazrian (Jurusan Aqidah dan Filsafat Islam Fakultas Ushuluddin dan Adab UIN Sultan Maulana Hasanuddin Banten, 2024)
Eschatology is one of the most important discussions in the religious field. Eschatology discusses everything related to the state of humans on the last day such as; death, apocalypse, heaven, and hell. In Islam, eschatology is known as al-Ma'ād. Belief in al-Ma'ād is an obligation required by the shari’ah. This study aims to explain the concept of eschatology regarding hell (al-nār) and heaven (al-jannāt) in the book Daqā'iq al-Akhbār Fī Żikri al-Jannāt wa an-Nār by al-Imam Abd ar-Rahīm al-Qāḍi. The research method is descriptive-analytical with a theological approach. The finding of this research is that al-Qāḍī's explanation of the concepts of hell and heaven is narrated with interesting stories with his classification of the two even though there is an exclusive reasoning about the path of salvation in his book. This study still highlights the book in the chapter on hell and heaven only, so the potential for other researchers to explore the ideas in the book further is still wide open in the future.